Do politicamente correto ao incorretamente polido - Neves, Maria Helena De Moura (Pontifícia Universidade Católica de São Paulo - PUC-SP, 2014)
The text argues that a linguistic analysis paired with the appreciation of the context of current social stands is highly legitimate, observing, however, that, in different situations, this so-called investigative-appreciative attitude has been transformed in actions and reactions that might become vulgarized in common place, or might even become disfigured in stupidity. The distortions in the assessment of the discourse of the other are now a widespread, the hunt for what is now conventionalized as the politically incorrect in language is just a sample of such a distortion. In this presentation, a number of cases of such a nature is analyzed against cases in which, inversely, the use of language is markedly polite, but the deviation of conduct is made more evident. The objective is to evaluate both cases via the role of intersubjectivity in the construal of discourse, aiming at verifying its conceptual counterpart, with special attention to evidence on the mutual conceptual engagement between interlocutors.

O texto defende que a ligação da análise da linguagem com a apreciação do contexto das posturas sociais do momento é algo absolutamente legítimo, observando, entretanto, que, em diversas situações, esse tipo de atitude investigativo-apreciativa vem sendo transformada em ações e reações que se banalizam no lugar-comum ou que, até, se desfiguram na insensatez. Distorções de avaliação do discurso do outro têm sido constantes, e disso é uma amostra gritante a caça que vem sendo feita, ao sabor de paixões irrefletidas, ao que se convencionou chamar de politicamente incorreto em linguagem. Na apresentação se avalia uma série de casos dessa natureza em confronto com casos em que, inversamente, a forma de uso se oferece como marcadamente polida, mas a incorreção de conduta é ainda mais evidente. O objetivo é avaliar um e outro caso por via do papel da intersubjetividade na condução do discurso, no sentido de verificar a contraparte conceptual da questão, especialmente as evidências, no enunciado, do engajamento conceptual dos envolvidos na enunciação.
From the politically correct to the incorrectly polite
Keywords: enunciation; intersubjectivity; politness; politically correct; enunciação; intersubjetividade; polidez; politicamente incorreto